Horizontal and vertical integration and securities trading and settlement - Jens Tapking; Jing Yang (European Central Bank (ECB), 2004)
This paper addresses a very European issue, the consolidation of securities trading and settlement infrastructures. In a two-country model, we analyze welfare implications of different types of consolidation. We find that horizontal integration of settlement systems is better than vertical integration of exchanges and settlement systems, but vertical integration is still better than no consolidation. These findings have clear policy implications with regards to the highly fragmented European securities infrastructure.
Keywords: G21; G15; L13; 330; Securities trading and settlement; substitutes and complements; vertical and horizontal integration